2023
DOI: 10.55643/fcaptp.5.52.2023.4149
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the Synthetic Indicator of Competitiveness of Agricultural Enterprises: A Methodological Approach to the Use of Neural Network Tools

Illia Chikov,
Olha Khaietska,
Okhota Yuliia
et al.

Abstract: The article is devoted to the development of a methodical approach to modelling a synthetic indicator of the competitiveness of agricultural enterprises using the tools of neural networks.The authors used general scientific and special research methods, such as monographic, logical-theoretical, statistical and economic-mathematical, visualization, system analysis, taxonomy and neural network modelling, generalization, logical abstraction and conclusion generation. The study was based on materials from the Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Bulakh (2023) stated that the viability of an e-commerce enterprise is primarily determined by the reliability and innovative nature of its cyber security system. Chikov et al (2023) indicate the need to use innovative financial tools, particularly blockchain, in the field of e-commerce. Zhao et al (2020) indicated a growing interest in e-commerce management for analysing big data, mainly to increase the effectiveness of their marketing strategies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bulakh (2023) stated that the viability of an e-commerce enterprise is primarily determined by the reliability and innovative nature of its cyber security system. Chikov et al (2023) indicate the need to use innovative financial tools, particularly blockchain, in the field of e-commerce. Zhao et al (2020) indicated a growing interest in e-commerce management for analysing big data, mainly to increase the effectiveness of their marketing strategies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Within the framework of the first stage, the assessment of competitiveness consists in recording the results of the competitive struggle of enterprises in the form of competitive advantages in comparison with their competitors. Taking into account the results of own researches described in works (Chikov, 2023), it is proposed to diagnose the competitiveness of agribusiness enterprises using the author's model based on the principles of artificial intelligence. Taking into account studies, which prove that models based on artificial intelligence allow to solve problems based on incomplete, "noisy", distorted information, this will allow to obtain reliable and objective results, reflecting the real state of functioning agribusiness enterprises (Matviychuk, 2010;Ruzakova, Yurchuk, 2021).…”
Section: Innovative Mechanism For Improving the Competitiveness Of Ag...mentioning
confidence: 99%